A comprehensive analysis towards benchmarking of life cycle assessment of buildings based on systematic review. (15th October 2021) - Dong, Yahong; Ng, S. Thomas; Liu, Peng
Abstract: The building industry is a sector of great importance to human beings and at the same time responsible for significant environmental degradations. In the past decades, life cycle assessment (LCA) has been increasingly applied to the building sector. To understand the life cycle environmental impacts of buildings, the emission levels of different environmental impact categories should be quantitatively analyzed by comparing LCA results of different case studies. In this study, comparative analyses of the impact assessment results of building case studies are conducted according to a systematic review approach. A total of 105 building cases published in the last decade are examined with a harmonized comparison. The whole life cycle of building, i.e., production, use and end-of-life are analyzed. Statistics for 7 impact categories and 3 damage categories are provided. Analysis is further conducted for different building structures: concrete, timber, and metal (steel or aluminum), as well as for different building types: residential and commercial. It is noted that the results of previous studies have large discrepancies. Nonetheless, the statistical medians of the selected building cases are found to be comparable with the recently published benchmarks. It is also found that climate change and energy depletion are not always the most significant impact categories. This study improves our understanding on the LCA outcomes of buildings and the results should help build a solid foundation for LCA practice in the building sector. Highlights: A total of 105 building cases published in the last decade are analyzed. The statistics and distribution for 7 individual categories are examined. Large discrepancies in results are observed for all the impact categories. The medians are found to compare favorably with existing benchmarks of buildings.